Dll1- and Dll4-mediated Notch signaling is required for homeostasis of intestinal stem cells - Pellegrinet, Luca (2011)
BACKGROUND & AIMS: Ablation of Notch signaling within the intestinal epithelium results in loss of proliferating crypt progenitors, due to their conversion into post-mitotic secretory cells. We aimed to confirm that Notch was active in stem cells (SC), investigate consequences of loss of Notch signaling within the intestinal SC compartment, and identify the physiological ligands of Notch in mouse intestine. Furthermore, we investigated whether the induction of goblet cell differentiation that results from loss of Notch requires the transcription factor Krüppel-like factor 4 (Klf4). METHODS: Trasgenic mice that carried a reporter of Notch1 activation were used for lineage tracing experiments. The in vivo functions of the Notch ligands Jagged1 (Jag1), Delta-like1 (Dll1), Delta-like4 (Dll4), and the transcription factor Klf4 were assessed in mice with inducible, gut-specific gene targeting (Vil-Cre-ERT2). RESULTS: Notch1 signaling was found to be activated in intestinal SC. Although deletion of Jag1 or Dll4 did not perturb the intestinal epithelium, inactivation of Dll1 resulted in a moderate increase in number of goblet cells without noticeable effects of progenitor proliferation. However, simultaneous inactivation of Dll1 and Dll4 resulted in the complete conversion of proliferating progenitors into post-mitotic goblet cells, concomitant with loss of SC (Olfm4+, Lgr5+ and Ascl2+). Klf4 inactivation did not interfere with goblet cell differentiation in adult wild-type or in Notch pathway-deficient gut. CONCLUSIONS: Notch signaling in SC and progenitors is activated by Dll1 and Dll4 ligands and is required for maintenance of intestinal progenitor and SC. Klf4 is dispensable for goblet cell differentiation in intestines of adult Notch-deficient mice.